Penggunaan Ubi Ungu dan Pisang Sebagai Bahan Baku Utama Pembuatan Inovasi Produk Snack Bar - Dewi Hermawati Wahyuningsih; Jasanta Peranginangin; Ivan Budi Prasetya (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
As the world of culinary creation develops, there are many food product innovations that, apart from being snacks, also contain the nutrients needed by the body. One of these foods is a snack bar. Snack bars are made to be a reliable source of high quality protein, fiber, vitamins and minerals and usually consumed by dieters for daily consumption or as snacks at certain times. Purple sweet potatoes and bananas are two food ingredients that are easy to get, especially in Indonesia, including Surakarta. These two food ingredients are usually processed for daily use because of their affordable prices, but most of them are traditional foods. This research aims to determine the process of making purple sweet potatoes and bananas into snack bars and find out respondents' opinions regarding this innovative snack bar product. The research methodology uses a qualitative method with an interview approach which is expressed descriptively using a questionnaire. The results of the research stated that the snack bar recipe formula was successful in finding the main raw materials of purple sweet potato and banana which were liked by respondents. The advice given is to improve the texture and durability of the finished snack bar product.